Biogenic Synthesis and Characterization of Zinc Oxide and Titanium Dioxide Nanoparticles Mediated by Plant Extracts - Sabrina. Benmebarek; Nadia Djouambi; Salima. Bacha; Imed Eddine Benmebarek; Bouzid Omar Boussaha; Aicha Beya Mammeria; Rabab Kadri (International Journal of Computational and Experimental Science and Engineering, 2026)
Abstract: Context: Nanotechnology, a multidisciplinary field involving physics, chemistry, and biology, offers major applications in biomedicine and dentistry due to the unique properties of nanomaterials. The green synthesis of nanoparticles (NPs), particularly from plant extracts, is a sustainable approach with advantages in terms of biocompatibility and reduction of harmful effects. Metal oxide nanoparticles, such as ZnO and TiO₂, are distinguished by their photocatalytic, magnetic, and antimicrobial properties due to their small sizes and large specific surface areas. In this study, ZnONPs and TiO₂NPs were synthesized using aqueous extracts of clove and olive leaves with a zinc salt (Zinc Nitrate) as pioneers and titanium dioxide due to its ability to catalyze chemical reactions and its efficiency in removing contaminants from the environment. Materials and methods: Different experimental techniques are used for the preparation, characterization and analysis of these nanoparticles, highlighting the ecological approach adopted in their synthesis. X-ray diffraction (XRD), infrared spectroscopy (FTIR), UV-visible spectroscopy, surface area determination analysis (BET) and X-ray fluorescence (XRF) were used to characterize the optical, chemical, crystalline, textural and elemental properties of the formed nanoparticles. Results: The green synthesized ZnONPs and TiO2NPs were initially confirmed using a UV-visible spectrophotometer. This technique was used to evaluate the optical properties of the nanoparticles and estimate the band gap size. The analysis allowed us to compare the absorption bands of the two types of nanoparticles, which eliminated interferences due to the solvent or the reference substrate, and to obtain an accurate absorption spectrum of the studied nanoparticles. Other analyses were carried out on these nanoparticles such as infrared (IR) spectroscopy analysis which allowed us to identify the functional groups involved in the stabilization of the nanoparticles. X-ray diffraction (XRD) was used to determine the crystal structure and crystallite size of the nanoparticles. The Brunauer–Emmett–Teller (BET) technique was used to measure the specific surface area of nanoparticles, a crucial data for catalytic and absorptive applications. The antimicrobial activity was tested for TiO₂ and ZnO nanoparticles synthesized from plant extracts against two bacterial strains: Staphylococcus aureus, Escherichia coli. Titanium dioxide nanoparticles showed the best overall efficacy against Gram-positive and Gram-negative bacteria while ZnO nanoparticles showed fair efficacy, but lower than TiO2 in the majority of cases. Conclusion: The study of antimicrobial activity highlighted a notable efficacy, in particular for TiO₂ nanoparticles associated with olive leaf and clove extracts, demonstrating a strong inhibitory power on Staphylococcus aureus and Escherichia coli.